Effects of a Comprehensive Reminder System Based on the Health Belief Model for Patients Who Have Had a Stroke on Health Behaviors, Blood Pressure, Disability, and Recurrence From Baseline to 6 Months: A Randomized Controlled Trial. Issue 2 (March 2020) - Wang, Meng-Yao; Shen, Meng-Jie; Wan, Li-Hong; Mo, Miao-Miao; Wu, Zhen; Li, Li-Li; Neidlinger, Susan H.
Abstract : Background: The health behaviors and blood pressure control of patients with hypertension who have had a stroke are unsatisfactory. A protocol of a comprehensive reminder system has been published, and the results of 3 months of implementation have demonstrated improved patient health behaviors and blood pressure control. The continuity of the intervention effect on these variables after 3 months was not clear. Objective: The aim of this study was to determine the impact of a comprehensive reminder system intervention on health behaviors, medication adherence, blood pressure, disability, and stroke recurrence in patients with hypertension who have had a stroke from baseline to 6 months after discharge. Method: A multicenter, assessor-blinded, randomized controlled trial was conducted with 174 patients with hypertension who have had a stroke. The intervention consisted of health belief education, a calendar handbook, weekly short message services, and telephone interviews. Data were collected at baseline and at 3 and 6 months after discharge. Results: Repeated-measures analysis of variance and single-effect analysis revealed that, compared with the control group, improvements of health behaviors, medication adherence, blood pressure, and disability of participants in the intervention group were superior. From 3 to 6 months after discharge, these trends remained or continually improved, whereas a downward trend was observed in the control group. There were only 2 stroke recurrences within 6 months, and no statistically significant difference between groups was found. Conclusion: The comprehensive reminder system improved patients' health behaviors and medication adherence and reduced blood pressure and disability; the effect extended to 6 months after discharge.